2000
DOI: 10.1523/jneurosci.20-15-05880.2000
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Currently Relevant Memories by the Human Posterior Medial Orbitofrontal Cortex

Abstract: We have demonstrated previously that patients producing spontaneous confabulations fail to suppress currently irrelevant memory traces, so that they act and think on the basis of a false, temporally displaced (past) reality. All spontaneous confabulators had anterior limbic damage, in particular of the orbitofrontal cortex and basal forebrain. These findings indicated that these structures are essential for distinguishing between mental representations of ongoing reality and currently irrelevant memories. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 54 publications
9
87
1
2
Order By: Relevance
“…In adults, the mechanism depended on the orbitofrontal cortex: lesions always involved the posterior medial orbitofrontal cortex (area 13) or directly connected structures (Schnider, 2008;Schnider et al, 1996a;Schnider & Ptak, 1999). Functional imaging studies in healthy subjects showed activation in the orbitofrontal cortex area 13 in the second run of continuous recognition tasks, either when using pictures (Schnider, Treyer, & Buck, 2000;Treyer, Buck, & Schnider, 2003) or meaningful sounds (Treyer, Buck, & Schnider, 2006). The mechanism underlying orbitofrontal reality filtering appears to be similar to extinction capacity, the ability to abandon anticipations that are no longer valid (Nahum, Ptak, Leemann, & Schnider, 2009).…”
mentioning
confidence: 99%
“…In adults, the mechanism depended on the orbitofrontal cortex: lesions always involved the posterior medial orbitofrontal cortex (area 13) or directly connected structures (Schnider, 2008;Schnider et al, 1996a;Schnider & Ptak, 1999). Functional imaging studies in healthy subjects showed activation in the orbitofrontal cortex area 13 in the second run of continuous recognition tasks, either when using pictures (Schnider, Treyer, & Buck, 2000;Treyer, Buck, & Schnider, 2003) or meaningful sounds (Treyer, Buck, & Schnider, 2006). The mechanism underlying orbitofrontal reality filtering appears to be similar to extinction capacity, the ability to abandon anticipations that are no longer valid (Nahum, Ptak, Leemann, & Schnider, 2009).…”
mentioning
confidence: 99%
“…This function has also been specifically linked to the anterior limbic system, of which the orbitofrontal cortex is a central component (Schnider, Treyer and Buck, 2000;Treyer et al, 2003). Most recently, Gilboa, Moscovitch and colleagues (Gilboa, 2004;Gilboa and Moscovitch, 2002;Gilboa et al, 2006) have suggested that confabulation results from failure of a monitoring system which facilitates early, intuitive rejection of false memories o n t h e b a s i s o f " f e e l i n g o f r i g h t n e s s " .…”
mentioning
confidence: 99%
“…When subjects do such a task for the first time, they can recognize picture repetitions on the sole basis of familiarity (Figure 2A). Healthy subjects performing such a first run activated the hippocampal area (Schnider et al, 2000b). As subjects repeat the task, always composed of the same picture series, familiarity alone is not sufficient anymore; all items look familiar.…”
Section: Exploring the Sense Of Realitymentioning
confidence: 99%
“…When healthy subjects performed repeated runs of this task, they had activation of the posterior medial orbitofrontal cortex, area 13 ( Figures 1B,C) (Schnider et al, 2000b), which corresponds to the area of maximal damage in patients who confuse reality.…”
Section: Exploring the Sense Of Realitymentioning
confidence: 99%